2016
DOI: 10.21037/atm.2016.12.26
|View full text |Cite
|
Sign up to set email alerts
|

Companion diagnostics—a tool to improve pharmacotherapy

Abstract: The variability of pharmacotherapy can be of a significant magnitude, and the main reason for this is often diseases heterogeneity. Patients who have similar diagnoses very often respond differently to the same pharmacological intervention, with great variability in both efficacy and safety outcome. Despite having discussed personalized medicine for more than a decade, we still see that most drug prescriptions for severe chronic diseases are largely based on 'trial and error' and not on solid biomarker data. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(40 citation statements)
references
References 25 publications
0
40
0
Order By: Relevance
“…1 A well-known example of a commercialized theranostic is the use of HercepTest ® (Agilent, Santa Clara, CA, USA) in combination with Herceptin ® (Genentech, South San Francisco, CA, USA) for treating breast cancer. 2 However, this approach requires the sequential administration of the paired Dx/Rx agents. A more desirable and potentially straightforward approach would be the simultaneous administration of the Dx/Rx agents to shorten procedure times while potentially improving patient comfort.…”
Section: Introductionmentioning
confidence: 99%
“…1 A well-known example of a commercialized theranostic is the use of HercepTest ® (Agilent, Santa Clara, CA, USA) in combination with Herceptin ® (Genentech, South San Francisco, CA, USA) for treating breast cancer. 2 However, this approach requires the sequential administration of the paired Dx/Rx agents. A more desirable and potentially straightforward approach would be the simultaneous administration of the Dx/Rx agents to shorten procedure times while potentially improving patient comfort.…”
Section: Introductionmentioning
confidence: 99%
“…In a phase II study conducted with tamoxifen, a high correlation between a positive estrogen receptor status and response to the treatment was observed. Based on this finding the investigators suggested that the estrogen receptor assay should be used as a means to select patients for treatment with tamoxifen . Despite that this phase II study showed the significance of combining drug and diagnostics, it was not until the end of the 1990s that the first companion diagnostic obtained regulatory approval .…”
Section: Companion and Complementary Diagnostics: Definitions And Termentioning
confidence: 99%
“…Based on this finding the investigators suggested that the estrogen receptor assay should be used as a means to select patients for treatment with tamoxifen . Despite that this phase II study showed the significance of combining drug and diagnostics, it was not until the end of the 1990s that the first companion diagnostic obtained regulatory approval . Here the US‐based biotech company, Genentech (South San Francisco, CA), developed trastuzumab (Herceptin, Roche/Genentech) for the treatment of human epidermal growth factor receptor 2 (HER2)‐positive metastatic breast cancer.…”
Section: Companion and Complementary Diagnostics: Definitions And Termentioning
confidence: 99%
See 1 more Smart Citation
“…However, identifying patients who would benefit from bevacizumab therapy has been challenging, particularly because there are no companion diagnostics for monitoring or predicingt response to treatment. To date, pharmacotherapy for ovarian cancer has had variable success (13). As a result, there is an urgent need to develop novel targeted agents as well as companion diagnostics for cancer therapy.…”
Section: Abstract Ovarian Cancer Is the Most Lethal Malignancymentioning
confidence: 99%